Factors of a person’s religiosity in the context of overcoming the consequences of traumatic experience - Sharipova, Daria R. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The review of studies that have revealed the peculiarities of religious coping behaviour of individuals with traumatic experiences has been carried out. Psychological and social factors of religiosity of a person in the context of overcoming the consequences of a traumatic event are determined. The impact of religious motivation, God’s image, locus of control, active life position and religious group support on working through the psychological trauma by a person is revealed. Positive and negative influence of religious coping on an individual is presented. The compensatory and meaning-forming functions of religiosity is revealed. It is established that the living of a traumatic situation by a person depends not as much on the presence of religiosity as on the peculiarities of religion. It is noted that religiosity can both promote and hinder a person’s adaptation.